A cytokine-like protein Dickkopf-related protein 3 is atheroprotective - Yu, Baoqi; Niehrs, Christof (Circulation, 2017)
Background:Dickkopf-related protein 3 (DKK3) is a secreted protein that is involved in the regulation of cardiac remodeling and vascular smooth muscle cell differentiation, but little is known about its role in atherosclerosis.Methods:We tested the hypothesis that DKK3 is atheroprotective using both epidemiological and experimental approaches. Blood DKK3 levels were measured in the Bruneck Study in 2000 (n=684) and then in 2005 (n=574). DKK3-deficient mice were crossed with apolipoprotein E-/- mice to evaluate atherosclerosis development and vessel injury-induced neointimal formation. Endothelial cell migration and the underlying mechanisms were studied using in vitro cell culture models.Results:In the prospective population-based Bruneck Study, the level of plasma DKK3 was inversely related to carotid artery intima-media thickness and 5-year progression of carotid atherosclerosis independently from standard risk factors for atherosclerosis. Experimentally, we analyzed the area of atherosclerotic lesions, femoral artery injury-induced reendothelialization, and neointima formation in both DKK3-/-/apolipoprotein E-/- and DKK3+/+/apolipoprotein E-/- mice. It was demonstrated that DKK3 deficiency accelerated atherosclerosis and delayed reendothelialization with consequently exacerbated neointima formation. To explore the underlying mechanisms, we performed transwell and scratch migration assays using cultured human endothelial cells, which exhibited a significant induction in cell migration in response to DKK3 stimulation. This DKK3-induced migration activated ROR2 and DVL1, activated Rac1 GTPases, and upregulated JNK and c-jun phosphorylation in endothelial cells. Knockdown of the ROR2 receptor using specific siRNA or transfection of a dominant-negative form of Rac1 in endothelial cells markedly inhibited cell migration and downstream JNK and c-jun phosphorylation.Conclusions:This study provides the evidence for a role of DKK3 in the protection against atherosclerosis involving endothelial migration and repair, with great therapeutic potential implications against atherosclerosis.
Gesehen am 31.10.2018